Acute-on-chronic liver failure: definition, prognosis and management. Issue 6 (25th November 2019) - Amin, Ahmed; Mookerjee, Rajeshwar P
Abstract : Acute-on-chronic liver failure (ACLF) is a recently described entity in chronic liver disease defined by acute hepatic decompensation, organ failure and a high risk of short-term mortality (usually less than 4 weeks). This condition is distinct from acute liver failure and stable progression of cirrhosis in numerous ways, including triggering precipitant factors, systemic inflammation, rapid progression and a potential for recovery. While a clear definition of ACLF has been forwarded from a large European Consortium study, some heterogeneity remains in how patients present and the types of organ failure, depending on whether they are described in Asian or European studies. Active alcoholism, acute alcoholic hepatitis and infections are the most frequent precipitants for ACLF. Underpinning the pathophysiology of ACLF is a state of persistent inflammation and immune dysfunction, collectively driving a systematic inflammatory response syndrome and an increased propensity to sepsis. Prevention and early treatment of organ failure are key in influencing survival. Given increasing organ shortage and more marginal grafts, liver transplantation is a limited resource and emphasises the need for new therapies to improve ACLF outcomes. Recent data indicate that liver transplantation has encouraging outcomes even in patients with advanced ACLF if patients are carefully selected during the permissive window of clinical presentation. ACLF remains a significant challenge in the field of hepatology, with considerable research and resource being channelled to improve upon the definition, prognostication, treatment and unravelling of mechanistic drivers. This Review discusses updates in ACLF definition, prognosis and management.